1999
DOI: 10.1109/3.806596
|View full text |Cite
|
Sign up to set email alerts
|

Ge-on-Si approaches to the detection of near-infrared light

Abstract: We review our recent results on Ge-based near-infrared photodetectors grown on silicon. We fabricated metal-semiconductor-metal photodetectors based on epitaxial pure-Ge grown on silicon by Chemical Vapor Deposition, Material characterization and device performances are illustrated and discussed. Exploiting a novel approach based on evaporation of polycrystalline-Ge on silicon, we also realized efficient near-infrared photodiodes with good speed and sensitivity. Finally, multiple-element devices were designed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(48 citation statements)
references
References 31 publications
0
48
0
Order By: Relevance
“…The sleeves were used to extract photocurrent without substantially changing the antenna characteristics (from a bare dipole). Crystalline germanium was chosen to be the active material of our photodetector because of its high responsivity at near-infrared wavelengths and its compatibility with standard silicon technology 18 . Previous research has shown that use of a substrate with a high dielectric constant significantly weakens the antenna resonant strength 13 .…”
mentioning
confidence: 99%
“…The sleeves were used to extract photocurrent without substantially changing the antenna characteristics (from a bare dipole). Crystalline germanium was chosen to be the active material of our photodetector because of its high responsivity at near-infrared wavelengths and its compatibility with standard silicon technology 18 . Previous research has shown that use of a substrate with a high dielectric constant significantly weakens the antenna resonant strength 13 .…”
mentioning
confidence: 99%
“…This enables a significant reduction in the dislocation density of the as-grown Ge epilayer, thereby improving the detector's dark current performance. In yet another approach, Colace et al (1999) proposed a direct hetero-epitaxy growth of Ge on Si through the use of a low temperature thin SiGe buffer layer (a few 10nm). The insertion of such thin buffer avoids the occurrence of 3D SK growth, and allows the misfit dislocations to be concentrated at the hetero-interfaces.…”
Section: Hetero-epitaxy Of Germanium On Siliconmentioning
confidence: 99%
“…For particular photonic functions like light amplification and electrically pumped lasers at telecom wavelengths, the InP/InGaAsP material system remains the material of choice, despite significant research in Silicon based active opto-electronic devices [2] [3]. For detection of light at telecom wavelengths, both InP/InGaAsP and Germanium are being envisaged for integration on a Silicon platform [4] [5]. Therefore, in this paper we will focus on the integration of InP/InGaAsP laser diodes and photodetectors on top of an SOI waveguide circuit.…”
Section: Introductionmentioning
confidence: 99%